Frailty score and outcomes of patients undergoing vascular surgery and amputation: A systematic review and meta-analysis - Chen, Shujie; Dunn, Riley; Jackson, Mark; Morley, Nicola; Sun, Jing (Frontiers in Cardiovascular Medicine, 2023)
Introduction Frailty is associated with adverse postoperative health outcomes, including increased mortality, longer length of stay, higher rehospitalization, and other complications. There are many frailty assessment tools are to assess the level of frailty in vascular surgery patients. The aim of this study was to perform a systematic review and meta-analysis to assess the association between the frailty levels described by different frailty scores and adverse postoperative health outcomes among hospitalized vascular surgery patients and patients undergoing amputation. Methods Studies utilizing frailty scores and similar frailty assessment tools to describe frailty and investigate the association between frailty and health outcomes were searched. The primary outcomes of this study were in-hospital mortality, postdischarge mortality, length of hospital stay, rehospitalization, and discharge location. Additional outcomes included postoperative myocardial infarction, postoperative renal failure, cerebrovascular accident and stroke, comorbidities, and estimated glomerular filtration rate (eGFR) levels. Joanna Briggs Institute (JBI) Critical Appraisal Tools were used for quality assessment. Results In total, 24 studies with 1,886,611 participants were included in the final analysis. The overall results found that higher in-hospital mortality and postdischarge mortality were significantly associated with frailty. Frailty was also found to be significantly associated with a longer length of hospital stay, higher rehospitalization, and higher likelihood of non-home discharge. In addition, the results also showed that frailty was significantly associated with all kinds of comorbidities investigated, except chronic kidney disease. However, lower eGFR levels were significantly associated with frailty. Conclusion Among patients who underwent all types of vascular surgery and those who underwent amputations, assessment of frailty was significantly associated with adverse postoperative outcomes and multiple comorbidities. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=336374, identifier CRD42022336374.